Clinical features and oncological outcomes of primary female urethral cancer. Issue 5 (20th January 2022) - Lee, Wonchul; Yu, Jesang; Lee, Jae‐Lyun; Kim, Young Seok; Hong, Bumsik
Abstract: Purpose: Investigation of the clinical features and treatment outcomes of primary female urethral cancer (FUC) at a single institution. Materials and Methods: We retrospectively reviewed 32 FUC patients during 1997–2017. We investigated preoperative risk factors predicting overall (overall survival [OS]) and recurrence‐free survival (RFS) and reviewed clinical features, treatment modality, and oncologic outcomes according to pathology. The median follow‐up duration and age was 56 months (range: 4–229) and 61 years (range: 15–82), respectively. Results: The median OS and RFS were 70 and 16 months, respectively. A total of 19 (59.4%) patients received systemic chemotherapy, including 14 (43.8%) who received radiation therapy. Further, 22 patients (68.8%) underwent surgery. On univariate analysis, >T2, N+, and tumor size ≥3 cm were associated with poorer OS. There were 15 cases of distant metastasis and five local recurrences. Outcomes were poorest in adenocarcinoma (AC), moderate in clear cell carcinoma and transitional cell carcinoma, and best in squamous cell carcinoma (SCC). Conclusion: Female urethral lesions should be carefully examined to exclude FUC. Distal urethral SCC was responsive to surgical excision, but proximal urethral AC had poor oncological outcome even after extensive treatment. Due to the heterogeneity and poor prognosis of FUC, multimodal treatment is mandatory.